(untitled) (Journal of the College of Basic Education, 2022)
Oral administration of (20 mg/ml), of Acetamidine the active ingradiant of mospilan 20SG , the neonicotinoid insecticide that is effective against both soil and plant insects (LD50=200mg), for 30 days in male albino mice aged (6-7weeks), resulted Histopathologically significant alterations in the lungs included marked. Haemorrhage and inflammatory cells infiltration and thickening in connective tissue stroma. The oral toxicity study of Acetamidine revealed that this neonicotinoid insecticide is of highly risk in albino mice.